2016
DOI: 10.1371/journal.pone.0161746
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Phenotypic Variation in an Introgression Line Population Derived from an Interspecific Cross between Oryza glaberrima and Oryza sativa

Abstract: The introduction of closely related species genomic fragments is an effective way to enrich genetic diversity and creates new germplasms in crops. Here, we studied the genetic diversity of an introgression line (IL) population composed of 106 ILs derived from an interspecific tetra cross between O. glaberrima and O. sativa (RAM3/Jin23B//Jin23B///YuetaiB). The proportion of O. glaberrima genome (PGG) in the ILs ranged from 0.3% to 36.7%, with an average value of 12.32% which is close to the theoretically expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Miah et al [19] also reported the recurrent parent genome content in the selected BC 2 F 2 lines ranging from 92.7% to 97.7% using SSR markers. Chen et al [20], in their study of genetic diversity and phenotypic variation in an introgression line population of an interspecific Oryza glaberrima and Oryza sativa (RAM3/Jin23B//Jin23B///YuetaiB), revealed the proportion of the Oryza glaberrima genome (PGG) in the ILs ranging from 0.3% to 36.7%, with an average value of 12.32%.…”
Section: Discussionmentioning
confidence: 99%
“…Miah et al [19] also reported the recurrent parent genome content in the selected BC 2 F 2 lines ranging from 92.7% to 97.7% using SSR markers. Chen et al [20], in their study of genetic diversity and phenotypic variation in an introgression line population of an interspecific Oryza glaberrima and Oryza sativa (RAM3/Jin23B//Jin23B///YuetaiB), revealed the proportion of the Oryza glaberrima genome (PGG) in the ILs ranging from 0.3% to 36.7%, with an average value of 12.32%.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of germplasm from relative species such as African rice is an effective way to broaden the GDs of rice (Chen et al., 2016). In this study, correlation analysis showed that PGG was positive correlated with GDs between the ILs and the test variety ST1, indicating that the introduction of African rice genomic fragments into Asian rice genome could effectively increase the GD of parents of PIHs.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that the introduction of African rice genomic fragments into genomes of Asian rice could induce great heterosis of yield‐related traits in PIHs, which were generated by crosses between the ILs and indica rice cultivars, and the optimal PGG for different ILs was estimated to be 10–20% and 15–30% for hybrid rice breeding purpose respectively, i.e. the PGG in these ranges may be optimal between gaining positive effect of broadening the GD and avoiding negative effect of introducing unfavorable genes such as interspecific sterility loci (Adedze et al., 2016; Chen et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations